2010
DOI: 10.1002/pdi.1530
|View full text |Cite
|
Sign up to set email alerts
|

Does diabetes put you at risk of tetanus?

Abstract: This 81-year-old man with a history of type 2 diabetes presented with a cramping right arm, trismus, stiffness in the jaw, swallowing and breathing difficulties. He developed respiratory failure shortly after admission so was intubated on the intensive therapy unit where he received tetanus immunoglobulin and a course of metronidazole. Kilic et al. compared the level of tetanus antitoxin between patients with type 2 diabetes and healthy controls. They found a statistically significant difference between the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Infection does not develop in all diabetic foot ulcers; patients should be assessed for infection based on local evidence of inflammation (pain or tenderness, swelling or induration, warmth, erythema) as well systemic signs such as fever or manifestations of sepsis . Passive national surveillance from 2001 to 2008 in the US found that 15% of patients diagnosed with tetanus also had DM, triple the rate of the general population over that period (Centers for Disease Control and Prevention, 2011), indicating a need for more intensive attention to tetanus toxoid vaccination status in patients with DM (Soulsby and Russell-Jones, 2010). The prevalence of MRSA in diabetic foot infections ranges from 5% to 30% and continues to rise, complicating selection of empiric antibiotic coverage.…”
Section: Diabetic Foot Infections and Charcot Neuroarthropathymentioning
confidence: 99%
“…Infection does not develop in all diabetic foot ulcers; patients should be assessed for infection based on local evidence of inflammation (pain or tenderness, swelling or induration, warmth, erythema) as well systemic signs such as fever or manifestations of sepsis . Passive national surveillance from 2001 to 2008 in the US found that 15% of patients diagnosed with tetanus also had DM, triple the rate of the general population over that period (Centers for Disease Control and Prevention, 2011), indicating a need for more intensive attention to tetanus toxoid vaccination status in patients with DM (Soulsby and Russell-Jones, 2010). The prevalence of MRSA in diabetic foot infections ranges from 5% to 30% and continues to rise, complicating selection of empiric antibiotic coverage.…”
Section: Diabetic Foot Infections and Charcot Neuroarthropathymentioning
confidence: 99%